Reframing Surah Yasin: An Interdisciplinary Analysis of Qur’anic Cosmology, Astronomy, and Environmental Systems - Moh. Nadhif; Djunaidi Ghony; Junaidi Mistar; Bakri Muhammad Bakhiet (Nizham Jurnal Studi Keislaman, 2026)
This study critically reinterprets Surah Yasin beyond its dominant ritualistic framing by developing an interdisciplinary model of Qur’anic cosmology that integrates Qur’anic exegesis, Islamic astronomy, and environmental science. Existing scholarship on the Qur’an and science remains largely fragmentary, relying on verse-based analyses that overlook the structural coherence of a single surah as a unified system of meaning. Addressing this gap, the study employs a qualitative library-based approach using thematic tafsir combined with interdisciplinary analysis of celestial and environmental phenomena. The findings demonstrate that Surah Yasin presents a systemic representation of the cosmos, encompassing celestial motion, orbital dynamics (falak), temporal cycles, and ecological processes as interconnected components within a coherent framework. This integrated structure reflects patterned regularities that align conceptually with contemporary scientific perspectives without reducing the Qur’anic text to scientific claims. The study concludes that Surah Yasin can be conceptualized as a model of Qur’anic cosmology that functions as an epistemological framework for understanding the relationship between revelation and the natural world. This research contributes to advancing interdisciplinary discourse on Islam and science by shifting the analytical focus from fragmented verse-based interpretation toward a surah-based systemic paradigm.